Coinfection of tuberculosis and COVID-19 limits the ability to in vitro respond to SARS-CoV-2. (December 2021) - Petrone, Linda; Petruccioli, Elisa; Vanini, Valentina; Cuzzi, Gilda; Gualano, Gina; Vittozzi, Pietro; Nicastri, Emanuele; Maffongelli, Gaetano; Grifoni, Alba; Sette, Alessandro; Ippolito, Giuseppe; Migliori, Giovanni Battista; et al.
Highlights: TB and COVID-19 coinfection does not affect M. tuberculosis -specific response. TB and COVID-19 coinfection limits the ability to in vitro respond to SARS-CoV-2. Latent TB infection does not affect the ability to in vitro respond to SARS-CoV-2. Abstract: Objectives: The interaction of COVID-19 and tuberculosis (TB) are still poor characterized. Here we evaluated the immune response specific for Micobacterium tuberculosis (Mtb) and SARS-CoV-2 using a whole-blood-based assay-platform in COVID-19 patients either with TB or latent TB infection (LTBI). Methods: We evaluated IFN-γ level in plasma from whole-blood stimulated with Mtb antigens in the Quantiferon-Plus format or with peptides derived from SARS-CoV-2 spike protein, Wuhan-Hu-1 isolate (CD4-S). Results: We consecutively enrolled 63 COVID-19, 10 TB-COVID-19 and 11 LTBI-COVID-19 patients. IFN-γ response to Mtb-antigens was significantly associated to TB status and therefore it was higher in TB-COVID-19 and LTBI-COVID-19 patients compared to COVID-19 patients (p ≤ 0.0007). Positive responses against CD4-S were found in 35/63 COVID-19 patients, 7/11 LTBI-COVID-19 and only 2/10 TB-COVID-19 patients. Interestingly, the responders in the TB-COVID-19 group were less compared to COVID-19 and LTBI-COVID-19 groups (p = 0.037 and 0.044, respectively). Moreover, TB-COVID-19 patients showed the lowest quantitative IFN-γ response to CD4-S compared to COVID-19-patients (p = 0.0336) and LTBI-COVID-19 patients (p = 0.0178). Conclusions: Our data demonstrate that COVID-19 patients either TB or LTBI have a low ability to build an immune response to SARS-CoV-2 while retaining the ability to respond to Mtb-specific antigens.